Analisis Pemahaman Konsep Sosialisasi Dan Internalisasi Nilai Budaya Dalam Sikap Menjunjung Tinggi Persatuan Masyarakat Di Desa Pancasila Kecamatan Natar Kabupaten Lampung Selatan - S Vianita Zulyan; Pargito Pargito; Pujiati Pujiati (Faculty of Teacher Training and Education, University of Lampung, 2019)
This study aims to analyze and explain the understanding of the concept of socialization and internalization of cultural values in an attitude of upholding community unity in the Pancasila. The results of this study conclude that 1) Understanding the concept of socialization in upholding community unity in the Pancasila Village is in the category of